La réciprocité comme déterminant de l’espace éducatif : le care permet-il de repenser l’éducation politique à la liberté ? - Sébastien Charbonnier (Éducation et Socialisation)
By the standards of care theories, this article offers a critical of the moral concept of autonomy so as to think political education to freedom. In a deterministic perspective, the reasoning takes into account our vulnerability and our fragility within the interdependencies that form and transform the human beings. As a consequence, learning of reciprocity becomes central: on one hand, “giving care”, “caring of” and “taking care of”, on the other hand, “care receiving”. Political education to freedom is learning to take care of each other, especially to talk and to listen: what may seem a truism is not obvious at all since it requires epistemic and deontic equality between learners and teachers. The purpose of this article is to take seriously what means reciprocity of the care into political education of individuals.